The BackRoom. (Room Magazine, 2012)
An interview with Arwen Brenneman, a computer programmer and technical writer and works with The Wood and Water doula collective. She explains why her group is called Wood and Water, citing its rootedness of the wood and the flexibility of water. She describes the most challenging and rewarding aspects of being a doula including being on call because women do not labour on a schedule.